Recent progress in materials used towards corrosion protection of Mg and its alloys - Ghazanfari, Hadi; Hasanizadeh, Saber; Eskandarinezhad, Sara; Hassani, Soheil; Sheibani, Mohsen; Dordsheikh Torkamani, Alireza; Fakić, Belma (Journal of Composites and Compounds, 2020)
Magnesium has little resistance to corrosion and therefore its production and use are quite limited. The problem of corrosion associated with these alloys has been alleviated to some extent by the advantages obtained from fine coatings. An additional dense barrier against corrosion is created, using coatings obtained from sol-gel. As an alternative for Cr-based conversion coatings, rare-earth elements-based ones are been increasingly investigated for Mg and its alloys due to being eco-friendly. Because of chemical inertness, low friction, and high hardness, diamond-like carbon (DLC) coatings have exhibited the best protection for Mg and its alloys. In this review, we shed light on recent advancements in novel coatings for Mg alloys including hybrid, rare-earth conversion, composite polymeric (polymer composite is a multi-phase material in which reinforcing fillers are integrated with a polymer matrix), and DLC coatings.